Implementation of Islamic-Based Human Resource Management: An Analysis of Islamic Education Institutions in Thailand - M Fadhil Pangestu; Isra Hayati (Al-Fikru: Jurnal Ilmiah, 2023)
This research aims to analyze the implementation of human resource management at Darul Muhmin School Satun Thailand, focusing on its implementation, supporting and inhibiting factors. This school was chosen as the research location because it has implemented Islamic principles in the implementation of human resource management. The approach used in this research uses a qualitative analysis method based on phenomenological studies. The research informants were the principal and teachers. Data collection used observation, interview and documentation study techniques. The results showed that the implementation of human resource management at Darul Muhmin Satun Thailand school is based on Islamic principles, such as all teachers and employees are required to take part in Al-Quran learning every Thursday to improve their teaching skills, teaching training before the school year opens, and evaluations attended by all educators to reassess whether the program and all efforts have run properly or as expected. Supporting factors are that this institution has recruitment standards as well as training for the development of educators and regular evaluations so that the desired goals or results can be achieved. While the obstacles are facilities that do not meet international standards